Macrophage Migration Inhibitory Factor in Protozoan Infections - Marcelo T. Bozza; Yuri C. Martins; Letícia A. M. Carneiro; Claudia N. Paiva (Journal of Parasitology Research)
Macrophage migration inhibitory factor (MIF) is a cytokine that plays a central role in immune and inflammatory responses. In the present paper, we discussed the participation of MIF in the immune response to protozoan parasite infections. As a general trend, MIF participates in the control of parasite burden at the expense of promoting tissue damage due to increased inflammation.